Forest structure of three endemic species of the genus polylepis (Rosaceae) in central Perú [Estructura forestal de tres especies endémicas del género Polylepis (Rosaceae) en la Región Central del Perú] - Camel V. (2019)
Polylepis (Rosaceae) is the dominant tree genus in High-Andean forest ecosystems. These ecosystems are severely threatened, but little is known about their structure and functioning. We provide the first reports of the dasometric structure and spatial distribution of eight forests of Polylepis canoi, P. flavipila and P. rodolfovasquezii in the Central Peruvian Andes as fundamental information for management and conservation policies. We sampled all individuals ?1 cm of diameter at ground level (DGL) in 20 plots of 10x10 m in each forest, and measured total height (TH) and DGL. Also, we mapped the spatial distribution of the individuals in two plots of 30x30 m (X and Y axes). We found differences in the dasometric structure between forests of the same species, which, in some cases, were associated with climate, soil or elevation variables. However, no well-defined pattern was found. The allometric relationships of the linear and non-linear models did not differ widely with respect to the R2 nor to the Akaike (AIC) scores, indicating that the forests did not show a saturation of tree height with increasing diameter. In the P. canoi forests, individuals with diameters ?10 cm were the most abundant. In contrast, the forests of P. rodolfo-vasquezii showed a predominance of individuals with diameters ?10 cm, whereas P. flavipila presented an altered structure with no relationship between DGL and TH in one of the evaluated forests. The analysis of spatial distribution according to the Ripley’s K function on a small scale revealed that P. flavipila and P. canoi presented random patterns, whereas P. rodolfo-vasquezii showed an aggregate pattern. Finally, our results showed that even forests of the same species have different dasometric structures, whereas spatial patterns differ only between species. So, caution must be taken when extrapolating information between species or forests during ecological studies and conservation actions. © 2019, Asociacion Argentina de Ecologia. All rights reserved.